Pengaruh Komunikasi Dan Disiplin Kerja Terhadap Kinerja Selector Dengan Motivasi Kerja Sebagai Variabel Intervening Pada Bagian Produksi Blow PT. Asia Pramulia Surabaya - Alfina Rahmawati; Parwita Setya Wardhani; Tri Wahjoedi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to determine the Influence of Communication and Work Discipline on Selector Performance with Work Motivation as an Intervening Variable in the Blow Production Section at PT. Asia Pramulia Surabaya. This type of research is quantitative. The population studied in this study is the performance of the blow production selector at PT. Asia Pramulia Surabaya. The number of samples in this study was 89 respondents. The sampling technique used the slovin technique. The data collection technique used in this study was a questionnaire distributed to the performance of the blow production selector at PT. Asia Pramulia Surabaya. The data analysis technique used in this study was path analysis (Path Coefficient) with SEM-PLS software. The results of the study showed that the communication variable had a significant effect on work motivation, the work discipline variable had a significant effect on work motivation, the communication variable had a significant effect on selector performance, the work discipline variable had a significant effect on selector performance, the work motivation variable had a significant effect on selector performance, the communication variable did not have a significant effect on selector performance through work motivation as a mediating variable, and the work discipline variable had a significant effect on selector performance through work motivation as a mediating variable.